Impact of STATCOM and BFCL on the performance of distance relay and its improvement by adaptive setting for gridinteractive offshore wind and marine current farm - Kushwaha S.K.S.; Mohanty S.R.; Samuel P. (My University, 2025)
This study explores the impact of the dynamic impedance of static synchronous compensator (STATCOM) and bridge type fault current limiter (BFCL) on the performance of distance relay and its improvement by adaptive setting for Grid Interactive Offshore Wind and Marine-Current Farm. For assessments, analytical results are presented under different STATCOM settings, low voltage ride through (LVRT) condition, and different types of fault conditions. Moreover, the presence of STATCOM and BFCL significantly changes the apparent impedance characteristic of the studied system. It is also seen that the presence of STATCOM likely to induce an under reach and overreach problem of distance relay. Further, the LVRT capability is significantly affected as STATCOM supplies reactive power to offshore wind generators during a short circuit on the grid side. It is found that the grid integration of OWF and MCF with STATCOM and BFCL is likely to induce mis-coordination and subsequently deteriorate the performance of distance relay, leading to system security problems. Therefore, this study proposed an adaptive setting in order to eliminate the simultaneous influence upon the dynamic impedance due to incorporation of STATCOM and BFCL on the distance relay setting. The simulation results show the efficacy of the proposed adaptive setting. © 2020 The Institution of Engineering and Technology.